2020
DOI: 10.33928/bib.2020.02.102
|View full text |Cite
|
Sign up to set email alerts
|

Increasing status of non-native vascular plants in the Sefton Coast sand-dune system, north Merseyside, UK

Abstract: Over 460 non-native (alien) taxa were recorded in a Sefton Coast sand-dune vascular plant inventory, their proportion in the flora increasing after 1999. Between 2005/06 and 2018, twice as many non-native as native plants were found. An analysis of occurrences of native and non-native taxa in six major habitat types found that a higher proportion of aliens was present in scrub/woodland and disturbed ground, while native plants had more occurrences in fixed dunes/dune grasslands, dune heath and wetlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Only 5% of the vascular associates of E. variegatum were non-native, a much lower proportion than the 37% aliens for the dune flora as a whole (Smith, 2015). Smith (2020) found that Sefton dune wetlands supported a significantly lower number of non-natives than native vascular plants. He suggested that this is because alien plants are less likely to have evolved the adaptations needed to thrive in soils that are subjected to seasonal flooding and waterlogging, with associated low oxygen levels and high sulphide concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…Only 5% of the vascular associates of E. variegatum were non-native, a much lower proportion than the 37% aliens for the dune flora as a whole (Smith, 2015). Smith (2020) found that Sefton dune wetlands supported a significantly lower number of non-natives than native vascular plants. He suggested that this is because alien plants are less likely to have evolved the adaptations needed to thrive in soils that are subjected to seasonal flooding and waterlogging, with associated low oxygen levels and high sulphide concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…The only vegetation management during the study period was regular uprooting by volunteers of large numbers of seedling Hippophae rhamnoides (Sea Buckthorn), a shrub that was introduced to this coast in the 1890s and is extremely invasive (Isermann et al, 2007;Smith, 2009Smith, , 2020. Some evidence of rabbit (Oryctolagus cuniculus) grazing was apparent early in the study but, after about 2015, none was seen.…”
Section: Habitatsmentioning
confidence: 99%